Population Health and Economic Growth - Bloom, David E.; Canning, David (World Bank, Washington, DC, 2017)
Health is a direct source of human welfare and also an instrument for raising income levels. The authors discuss a number of mechanisms through which health can affect income, focusing on worker productivity, children's education, savings and investment, and demographic structure. As well as the impact of current illness, health may have large effects on prospective life spans and life cycle behavior. Studies suggest there may be a large effect of health and nutrition in uteri, and in the first few years of life, on physical and cognitive development and economic success as an adult. Macroeconomic evidence for an effect on growth is mixed, with evidence of a large effect in some studies. However, there is a possibility that gains from health may be outweighed by the effect of increased survival on population growth, until a fertility transition occurs. The low cost of some health interventions that have large-scale effects on population health makes health investments a promising policy tool for growth in developing countries. In addition, higher priority could be given to tackling widespread 'neglected' diseases that is, diseases with low mortality burdens that are not priorities from a pure health perspective, but that do have substantial effects on productivity.